Evaluating the role of SARS-CoV-2 target genes based on two nucleic acid assay kits - Zhu, Xuetong; Zhou, Fengyan; Zhou, Qi; Xu, Jiancheng (Frontiers in Public Health, 2022)
Background Effective isolation and early treatment of coronavirus disease 2019 (COVID-19) relies on rapid, accurate, and straightforward diagnostic tools. In response to the rapidly increasing number of cases, reverse transcription-quantitative polymerase chain reaction (RT-qPCR) assays for multiple target genes have become widely available in the market. Methods In total, 236 COVID-19 patients with positive results in both RT-qPCR and rapid antigen diagnosis (Ag-RDT) were enrolled in the study. The cycle threshold (Ct) was compared with different onset times and target genes. Comparison between groups was evaluated with the Kruskal-Wallis test and Dunn test. The correlation between target genes was analyzed by Spearman. Results In samples of Ct ≤ 21, Ct was different for the nucleocapsid (N), open reading frame 1ab (ORF1ab), and envelope (E) genes (P < 0.05). Mild COVID-19 patients within 7 days of onset accounted for 67.80% of all enrolled patients. At the above stage, all target genes reached the trough of Ct, and N genes showed lower values than the other target genes. The Ct of the ORF1ab and N gene in asymptomatic patients differed from those of mild patients within 7 days and more than 14 days of onset. The kits used in the study showed strong consistency among target genes, with all correlation coefficients >0.870. Conclusion RT-qPCR confirmed that the N gene performed well in Ct ≤ 21 and samples within 7 days of onset. Ag-RDT was discriminatory for patients within 7 days of onset. This study facilitated early identification and control of COVID-19 prevalence among patients.